2015
DOI: 10.1155/2015/296721
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K1 Exerts Antiproliferative Effects and Induces Apoptosis in Three Differently Graded Human Colon Cancer Cell Lines

Abstract: Vitamin K1 has been demonstrated as having anticancer potentiality mainly in liver cancer cells. Beyond the reported mechanisms of cancer inhibition (cell cycle arrest and induction of apoptosis), a possible control by vitamin K1 on molecules affecting cell growth could be hypothesized. In the literature, few (if any) data are available on its antitumor effects on colon cancer cells. Therefore, the aims of the study were to investigate in three differently graded human colon cancer cell lines (Caco-2, HT-29, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 33 publications
1
14
0
Order By: Relevance
“…In the present study, before co-administering VK1 and L.GG, their effects on colon cancer cells were checked separately. As already reported (10), the highest VK1 concentrations (100 and 200 µM) administered up to 72 h had a significant antiproliferative and proapoptotic effect in all the tested cells. On the contrary, VK1 administration induced the cell cycle arrest only in two cancer cell lines (Caco-2 and SW480) and required a prolonged time of treatment (72 h).…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study, before co-administering VK1 and L.GG, their effects on colon cancer cells were checked separately. As already reported (10), the highest VK1 concentrations (100 and 200 µM) administered up to 72 h had a significant antiproliferative and proapoptotic effect in all the tested cells. On the contrary, VK1 administration induced the cell cycle arrest only in two cancer cell lines (Caco-2 and SW480) and required a prolonged time of treatment (72 h).…”
Section: Discussionsupporting
confidence: 86%
“…VK, an essential nutrient associated with the clotting cascade, has also been demonstrated to have anticancer properties in a variety of cancer cell lines including colon cancer cells (7,(9)(10)(11)37). Many hypotheses have been formulated to explain its ability to inhibit the cell proliferation, including an active induction of the cell cycle arrest, the effects on differentiation and apoptosis with the involvement of the MAPK pathway (7,8) and the control on a class of molecules affecting cell growth such as polyamines (10,11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 ERK is usually known to prevent apoptosis, but several reports have proposed a different meaning of p-ERK. 41 The previous studies showed the pro-apoptotic role of ERK pathway. The sustained increase of ERK activity induced growth arrest and the suppression of p-ERK-inhibited apoptosis.…”
Section: Discussionmentioning
confidence: 98%
“…A key study regarding the IL‐6/STAT3 pathway showed that IL‐6 −/− mice developed fewer and smaller tumors and revealed downregulation of p‐STAT3 and BCL‐X L . ERK is usually known to prevent apoptosis, but several reports have proposed a different meaning of p‐ERK . The previous studies showed the pro‐apoptotic role of ERK pathway.…”
Section: Discussionmentioning
confidence: 99%